“Diya”-Related Burn Injuries during the Diwali Period: A 5-Year Retrospective Review from a Tertiary Care Hospital in India - Deepti Gupta; Nemi Chand; Nupoor Nanavati; Aakash Chauhan; Sujata Sarabahi (Indian Journal of Plastic Surgery)
Background Diwali is a festival that is passionately celebrated by Indians all across the globe. Fire hazards associated with this festival are well known. Our hospital is a tertiary care burn center and caters to a patient population from all over North India. Firecracker burns and diya burns constitute two major causes of burn injuries during the festival of Diwali. Since, diya-related burn injuries have been overlooked in the past, this study was primarily designed to study the demographical data of “diya burns” during Diwali.